If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 8 + 2m Solving 18 = 8 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 18 + -2m = 8 + 2m + -2m Combine like terms: 2m + -2m = 0 18 + -2m = 8 + 0 18 + -2m = 8 Add '-18' to each side of the equation. 18 + -18 + -2m = 8 + -18 Combine like terms: 18 + -18 = 0 0 + -2m = 8 + -18 -2m = 8 + -18 Combine like terms: 8 + -18 = -10 -2m = -10 Divide each side by '-2'. m = 5 Simplifying m = 5
| (x-1)x(x+1)=1320 | | 60.00+42.95=57.95 | | 0.20x+0.05(6-x)=0.10(30) | | a(5)+b(-9)=c | | 7x-8=-8+5 | | 3x+17=-10 | | -2(x-5)+10=10 | | -(-3a+1)=3a-1 | | 3(x+-2)=x+7 | | p^2+9p= | | 5x^2-10x+20=4x^2-2x+5 | | 3x+7=12x-4 | | 90+(10+8)= | | 2x+11=89-8x | | -3(x-5)=3 | | 8n+16=4n | | h(x)=x^3-4 | | i(7+9i)(7-9i)=0 | | 2x+5-4(x+1)=6x+8 | | 2x+4=6x-7 | | 16a+18b+5c+5c-4b-2a= | | 0.75x+0.05(20-x)= | | 42=3(2w-3h) | | 16+r=4(r+1) | | 41x(x)-12x+48=4x(x)(x)(x)-3x(x)-64x-48 | | 2(x+1)+4(4x+5)=92 | | X+3x=x+x+11 | | 66x+2484x-73=51(50x+40) | | 41x(x)-12x+48=4x(x)(x)(x)-3x(x) | | 3(1.5c+4)=-1 | | 41x(x)-12x+48=4x(x)(x)(x) | | (3x+1)=85 |